Fiscal foresight, limited information and the effects of government spending shocks - Fragetta, M.; Gasteiger, E. (Oxford Bulletin of Economics and Statistics, 2014)
We quantify the impact of government spending shocks in the US. Thereby, we control for fiscal foresight, a specific limited information problem (LIP) by utilizing the narrative approach. Moreover, we surmount the generic LIP inherent in vector autoregressions (VARs) by a factor-augmented VAR (FAVAR) approach. We find that a positive deficit- financed defence shock raises output by more than in a VAR (e.g. 2.61 vs. 2.04 for peak multipliers). Furthermore, our evidence suggests that consumption is crowded in. These results are robust to variants of controlling for fiscal foresight and reveal the crucial role of the LIP in fiscal VARs.